LABORATORY OF CLINICAL IMMUNOLOGY N.V. SKLIFOSOVSKY RESEARCH INSTITUTE FOR EMERGENCY MEDICINE (HISTORY AND PRESENT) - M. A. Godkov; G. V. Bulava (Неотложная медицинская помощь, 2016)
ABSTRACT. Assessment of the immune status of patients with urgent types of pathology in the Institute for Emergency Medicine is performed according to three main objects of research: humoral , phagocytic and lymphocytic components of immune system . This complex allows to fully and adequately evaluate the condition of the immune system of patients at different stages of traumatic disease and after transplantation of organs and tissues , to forecast the probability of septic complications developing, adjust the therapy . During 45 years of work of immunological service formed the algorithm of the adequate immunological screening was formed, number of innovative methods of diagnosis was developed, the ideology of post-test counseling of patients by immunologists was created, mathematical methods of storage, modeling and processing of research results was introduced. Laboratory staff identified a number of medical and social factors in the spread of blood-borne viral infections (HIV, hepatitis B and C). New organizational and economic methods of management team were introduced in the laboratory. The basis of the work is equal integration of scientific and clinical staff of the laboratory.